Phagotrophic protist-mediated control of polymyxa graminis in the wheat rhizosphere - Wu, Chuanfa; Ge, Chaonan; Wang, Fangyan; Zhang, Haoqing; Zhu, Zhenke; Lesueur, Didier Marcel Gerard; Yang, Jian; Chen, Jianping; Ge, Tida (Springer, 2023)
Uncovering potential biocontrol agents that suppress soil-borne pathogens is an important step toward developing sustainable management strategies for disease control and to maintain plant health. Plant cultivars influence rhizosphere microorganism mediated soil-borne disease control. However, the disease-resistance mechanisms and microbial taxa involved in the control of soil-borne mosaic virus are largely unknown. Methods We designed a field experiment on wheat cultivars for virus-resistance identification and conducted metagenomic analysis to determine the potential mechanisms used by rhizosphere microbial communities that affect the density of the mosaic virus vector- Polymyxa graminis, and to identify potential microbes that inhibit virus transmission. Results We found high P. graminis abundance and microbial diversity in the susceptible wheat cultivar rhizosphere. The relative abundance of indicative phagotrophs showed a strong negative correlation to P. graminis abundance during disease onset, indicating that predator–prey interactions influenced P. graminis activity. Moreover, we found strong and negative associations between the relative abundance of key ecological cluster, hub phagotrophic species and P. graminis abundance in multitrophic ecological networks. A structural equation model analyses indicated that phagotrophic protists were the main predictors of P. graminis abundance upon disease onset. Conclusion Our results demonstrate the important role of phagotrophic protists as top-down controllers for plant defense against pathogens. Our findings highlight the complexity of rhizosphere networks, reflecting the co-occurrence patterns of multi-trophic level microbes in virtual networks and strengthening the association between soil microbial diversity and plant health.